Peran Guru PKn dalam Menanamkan Sikap Anti-Diskriminasi di Lingkungan Sekolah Dasar - Liandy, Septian (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study examines the role of Civics (PKn) teachers in fostering anti-discrimination attitudes in elementary schools, aiming to analyze effective teaching strategies and identify implementation challenges. Using a qualitative library research method, the study analyzes academic literature from the past five years, with research subjects including journal articles, books, and policy documents, while the object focuses on teaching methods and barriers in anti-discrimination education. Data was collected through systematic searches of academic databases and analyzed using content analysis to identify patterns and gaps. Findings reveal that interactive methods like problem-based learning and role-playing are more effective than lectures, though challenges such as inadequate teacher training, curriculum overload, and socio-cultural influences persist. The study also highlights disparities between urban and rural schools and underutilized digital literacy opportunities. It concludes by recommending comprehensive teacher training, contextual learning materials, and multi-stakeholder collaboration to strengthen inclusive education.